PROCEEDINGS OF XIV CONGRESSO PORTUGUÊS DE TRANSPLANTAÇÃO AND XVII CONGRESSO LUSO BRASILEIRO DE TRANSPLANTAÇÃO - Associação Brasileira de Transplante de Órgãos (Brazilian Journal of Transplantation, 2019)
In this issue are presented abstracts of: CORNEA; BONES AND MISCELLANEOUS.